ChemInform Abstract: Chemical and Structural Characterization of Henryite, (Cu, Ag)3+xTe2 (x ≈ 0.40): A New Structure Type in the (Ag)—Cu—Te System. Issue 5 (February 2015) - Bindi, Luca
Abstract The crystal structure of the mineral henryite, a rare copper‐silver telluride, is solved using intensity data collected using a natural crystal from Campbell orebody, Bisbee, Arizona (USA).